1991
DOI: 10.1017/s0001867800023739
|View full text |Cite
|
Sign up to set email alerts
|

A bernoulli excursion and its various applications

Abstract: This paper is concerned with a random walk process in which and for i = 1, 2, ···, 2n . This process is called a Bernoulli excursion. The main object is to find the distribution, the moments, and the asymptotic distribution of the random variable ω n defined by . The results derived have various applications in the theory of probability, including random graphs, tournaments and order statistics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
101
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(106 citation statements)
references
References 21 publications
5
101
0
Order By: Relevance
“…This limit was first proved by Takács for simple lattice random walks [33] and was recently extended to all symmetric lattice random walks with a finite variance σ [48].…”
mentioning
confidence: 84%
“…This limit was first proved by Takács for simple lattice random walks [33] and was recently extended to all symmetric lattice random walks with a finite variance σ [48].…”
mentioning
confidence: 84%
“…The probability distribution of the area under a Brownian excursion was calculated exactly and is known as the Airy distribution function, a complicated function that involves the zeros of the Airy function but is not the Airy function itself [24,25,26,27,28]. This Airy distribution function has been a subject of intense study for the past several years as it has resurfaced in many problems in computer science [26,27], graph theory [29], and two dimensional polygon problems [30]. Recently it was shown that the same Airy distribution function also describes the distribution of maximal height in the stationary state of fluctuating interfaces [18,19].…”
Section: Exact Calculation Of the Restricted Propagator G +mentioning
confidence: 99%
“…and γ = 3/2 and B(·) is a scaling function. To analytically obtain the scaling exponent γ = 3/2 note that It is interesting to note that p(χ|τ ) in the case of free diffusion (corresponding to the limit D → ∞) has been previously considered by mathematicians [26][27][28] and shown to obey the scaling relation Eq. (5), with B given by the so-called Airy distribution [29,30].…”
mentioning
confidence: 99%